Supporting the end of prostitution permanently (SEPP) prostitution court: examining inter-professional collaboration within alternative criminal justice settings. Issue 2 (4th March 2021) - Blakey, Joan M.; Gunn, Alana J.; Canada, Kelli E.
ABSTRACT: Problem-solving courts such as prostitution courts are becoming an important feature of the American court landscape. Internationally, while there is a great deal of skepticism regarding problem solving courts, at least five countries (e.g., England, Scotland, Ireland, Australia, and Canada) are deliberating whether this "revolutionary panacea" which has swept America's criminal justice system is the right approach for them. Few studies have explored the benefits and challenges of problem solving courts (i.e. prostitution court) using an interprofessional collaborative framework. The purpose of this case study is to examine contemporary issues related to prostitution courts using Bronstein's model of interprofessional collaborative framework which identifies five components that facilitate optimum IPC: 1) interdependence, 2)newly created professional activities, 3)flexibility, 4)collective ownership of goals, and 5) reflection on the process . Some benefits of IPC include working collaboratively, adaptability, adjusting expectations, investment in the process and making changes as needed. Some of the challenges of IPC were coercive power, dual roles, bait and switch, hierarchy, and push for outcomes at the expense of clients. As criminal justice systems nationally and internationally contemplate widespread implementation of different kinds of problem-solving courts, these benefits and challenges need to be considered before states and countries adopt these courts.